The Semantical Analysis of “Boka” Custom Wedding In Buton - Andi Mulyani Kone; Chuzaimah Chuzaimah; Fatmalasari Fatmalasari (Fakultas Sastra - Universitas Muslim Indonesia, 2016)
This research is to explain analysis